Recognition, reconnection, and renewal: the meaning of money to sexual assault survivors - Holder, Robyn L. (International review of victimology, 2018)
Money as recompense for crime is variously described as making victims whole, restoring them to their pre-victimisation status, recognising the harm done, and facilitating closure and healing. This article explores the meaning of money to survivors of sexual victimisation and its place in their lives. Drawing on interviews with 20 female and male victims who applied for financial assistance to a state-administered scheme in Australia, we examine their motivations for applying, their reflections on the money received, and how they spent it. Claimants can receive two types of money in the overall financial assistance award: one for eligible expenses (or ‘economic loss') and another, the ‘special assistance' payment (for ‘non-economic loss' or what is termed ‘pain and suffering'), the latter of which they can spend in any way they wish. Most survivors applied for financial assistance because they required financial help, but upon receiving the ‘special assistance' payment, half said it meant acknowledgement by others. They spent this money on practical things, alone or in combination with items related to self-renewal and savings. In jurisdictions having a payment for ‘pain and suffering', we argue that its meaning is better conveyed to survivors as symbolic recognition of the wrong rather than a token recognition of the harm or injuries. If the aim of a scheme is victim recovery, emphasis should be placed on activities that enable survivors to reconnect with others and rebuild the self.